Cerebral Perforating Artery Disease: Characteristics on High-Resolution Magnetic Resonance Imaging - Liang, Jianye; Liu, Yiyong; Xu, Xiaoshuang; Shi, Changzheng; Luo, Liangping (Clinical neuroradiology (Munich), 2019)
Purpose Our aims were to evaluate the feasibility of high-resolution magnetic resonance imaging (HR-MRI) for displaying the cerebral perforating arteries in normal subjects and to discuss the value of HR-MRI for detecting the causes of infarctions in the territory of the lenticulostriate artery (LSA). Methods Included in this study were 31 healthy subjects and 28 patients who had infarctions in the territory supplied by the LSA. The T1-weighted imaging (T1WI), T2WI, diffusion-weighted imaging (DWI), and HR-MRI, including 3‑dimensional time-of-flight magnetic resonance angiography (3D-TOF-MRA) and 3D fast spin-echo T1WI (namely CUBE T1 in GE Healthcare), were applied on a 3-Tesla scanner. The numbers and route of the perforating arteries on both sides were independently confirmed on HR-MRI by two physicians. The Wilcoxon test was used to compare the differences. Results The numbers of perforating arteries in healthy subjects observed on 3D-TOF-MRA were as follows: numbers of the bilateral recurrent artery of Heubner (RAH) ranged from 0–3 (median 1), numbers of the left LSA ranged from 0–7 (median 3), numbers of the right LSA ranged from 0–5 (median 3), numbers of the bilateral anterior choroidal artery ranged from 1–2 (median 1) and the numbers of the bilateral thalamoperforating artery ranged from 1–2 (median 1). In the patients with lenticulostriate infarctions, the numbers of LSAs on the affected side were lower than on the opposite and ipsilateral sides in the healthy subjects. The results were statistically significant. An abnormality of the RAH may lead to a centrum semiovale infarct pattern, whereas an abnormality of the LSA is associated with a corona radiata infarct pattern. Conclusion The use of HR 3D-TOF-MRA and CUBE T1 had unique advantages in displaying the tiny perforating arteries in vivo. Moreover, effective recognition of the associated cerebral perforating artery and infarct patterns may enhance our understanding of the mechanism of stroke in patients with lenticulostriate infarctions.